2014
DOI: 10.1167/iovs.14-14706
|View full text |Cite|
|
Sign up to set email alerts
|

Mesothelial Cells: A Cellular Surrogate for Tissue Engineering of Corneal Endothelium

Abstract: Corneal endothelial cells and ATMCs share morphologic (structural) and marker (functional) similarities [corrected]. The ATMCs adhered and formed structures mimicking focal adhesion complexes with the HALC basal membrane. Monolayer structure and achieved density of ATMCs support the proposal to use adult human mesothelial cells (MCs) as a possible surrogate for damaged corneal endothelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…Transplanting the LC with the epithelial side down resulted in a more rapid recovery and a transparent cornea at 6 months when compared with control eyes. LC has also been used successfully as a scaffold for the expansion of both limbal epithelial stem cells and HCEnC in vitro (Kopsachilis et al, ; Lachaud et al, ; Navaratnam et al, ; Yoeruek et al, ). These data suggested that LC could eventually be used for human transplantation, but prior to in vivo use, further characterization is required.…”
Section: Discussionmentioning
confidence: 99%
“…Transplanting the LC with the epithelial side down resulted in a more rapid recovery and a transparent cornea at 6 months when compared with control eyes. LC has also been used successfully as a scaffold for the expansion of both limbal epithelial stem cells and HCEnC in vitro (Kopsachilis et al, ; Lachaud et al, ; Navaratnam et al, ; Yoeruek et al, ). These data suggested that LC could eventually be used for human transplantation, but prior to in vivo use, further characterization is required.…”
Section: Discussionmentioning
confidence: 99%
“…The known pluripotency of normal mesothelial cells has resulted in their use for tissue engineering, including replacement of neuralcrest derived corneal endothelium. 77 Our study has found that evidence of vascular differentiation in biopsies of MM varies greatly and Attanoos et al 73 found no CD31 expression in 92 mesotheliomas investigated, but all primary MM cells tested as part of our study were capable of VM in vitro.…”
Section: Discussionmentioning
confidence: 48%
“…Despite such interesting results, SF-based fibrous meshes have still not been applied to the manufacture a mesothelial tissue biomimetic. Similar positive outcomes with the use of mesothelial cells are likely to be expected, given their close phenotypic similarities with vascular endothelial cells (Chung-Welch et al, 1989 , 1997a , b ) and CECs (Jirsova et al, 2010 ; Lachaud et al, 2014b ).…”
Section: Clinical Sources Of Mesothelial Cellsmentioning
confidence: 74%